Enhancing the scientific argumentation skills of prospective chemistry teacher using integrated chemical literacy strategy - Sulistina, Oktavia; Rahayu, Sri; Dasna, I Wayan; Yahmin, Yahmin (Institute of Advanced Engineering and Science, 2024)
This research aims to enhance prospective chemistry teachers’ scientific argumentation skills through integrated chemical literacy strategy (ICLS) learning and to examine the patterns of relationship between students’ scientific argumentation skills in terms of content and socio-scientific issues (SSI). The study used mixed methods: the embedded design with embedded experimental model. The research sample was 88 students, the control and the experimental groups each consisted of 44 students. The research instrument used scientific argumentation skills test: an open and closed essay test, and interviews with 10 students as selected respondents. Data analysis used descriptive analysis, N-gain, Mann-Whitney test, effect size test, and qualitative analysis. The results showed that ICLS significantly had a great influence on enhancing students’ scientific argumentation skills. The interview results show that: the level of scientific argumentation skills related to SSI is not consistently related to content-related scientific argumentation skill; students who have scientific argumentation skills related to SSI levels 4, 3, and 2 can provide the correct claim, data, warrant, backing, and rebuttal to scientific arguments related to content if guided by guiding questions; student that had higher level of scientific argumentation skills need fewer guiding questions.